Endovascular treatment of inflammatory infrarenal aortic aneurysms - Bianchini Massoni, Claudio; Stein, Philipp von; Schernthaner, Melanie; Gallitto, Enrico; Rengier, Fabian; Katzen, Barry T.; Gargiulo, Mauro; Böckler, Dittmar; Geisbüsch, Philipp (Vascular and endovascular surgery, 2016)
OBJECTIVES: The aim of this study was to evaluate short- and midterm outcomes of endovascular aneurysm repair in patients with inflammatory abdominal aortic aneurysm (IAAA) focusing on changes in perianeurysmal inflammation and hydronephrosis. - METHODS: A retrospective study was performed considering data prospectively gathered from 1998 to 2013 in 3 centers. Patient demographics, preoperative clinical characteristics, clinical presentation, preoperative imaging measurements, procedural, and postoperative data were collected. Main outcome was to define evolution of periaortic fibrosis and hydronephrosis at computed tomography angiography (CTA) during follow-up. - RESULTS: A total of 22 patients (male n = 20; mean age 70.9 years ± 9.3) were included (mean AAA diameter: 58 mm ± 11, symptomatic: 50%, ruptured: 9.1%). Hydroureteronephrosis was preoperatively diagnosed by CTA in 6 (27.3%) cases. Median clinical follow-up was 2.2 years (range 0.1-14.5). Nine patients died during follow-up. At 1, 2, 4, and 6 years, overall survival was 85.4%, 74.3%, 56.6%, and 49.5%, respectively. Among these 13 patients with CTA follow-up, the mean AAA diameter was 56.2 mm ± 15.5, and progression of sac diameter was detected in 1 (7.7%) patient. Median maximum thickness of perianeurysmal inflammation was 5 mm (range 2-11) and decreased/remained unchanged in 92.3% of patients. Regression of hydroureteronephrosis occurred in 3 of 5 patients available for follow-up. There were no cases of de novo hydroureteronephrosis. - CONCLUSION: Endovascular treatment of IAAA has comparable short-term outcomes with non-IAAA. During midterm follow-up, aneurysm sac progression is rare, and perianeurysmal fibrosis decreases or remains unchanged in most cases. Hydronephrosis regression can occur in some but not all instances and thus warrants close surveillance.